2018
DOI: 10.1097/phm.0000000000000971
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Stimulation Enhances Task-Oriented Training for Moderate-to-Severe Hemiparesis 3–12 Months After Stroke

Abstract: Somatosensory stimulation can improve objective outcomes of motor training for moderate-to-severe hemiparesis less than 12 mos after stroke, although it needs to be determined whether the magnitude of between-groups differences in this study is clinically relevant. Future studies should investigate the intervention's impact on disability and functional recovery for this population as well as neurophysiological mechanisms underlying intervention effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…A second possible explanation for the lack of effect in our trial is the relatively low number of ESS-sessions (12-13) compared with higher number (18-28) in other studies. 30,54,55 Unfortunately, financial and logistical reasons prevented an ESS intervention beyond 4 weeks poststroke in this trial, and we cannot rule out that a longer intervention period might have altered the results. Likewise, we cannot rule out that using a standardized arm training protocol in which interventions such as neuromuscular electrical stimulation or robot-assisted therapy 59 prescribed to patients with severe impairments could have influenced the outcomes.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A second possible explanation for the lack of effect in our trial is the relatively low number of ESS-sessions (12-13) compared with higher number (18-28) in other studies. 30,54,55 Unfortunately, financial and logistical reasons prevented an ESS intervention beyond 4 weeks poststroke in this trial, and we cannot rule out that a longer intervention period might have altered the results. Likewise, we cannot rule out that using a standardized arm training protocol in which interventions such as neuromuscular electrical stimulation or robot-assisted therapy 59 prescribed to patients with severe impairments could have influenced the outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…Importantly, this conclusion rests on a very limited amount of data. Recently, an RCT 54 in subacute/chronic stroke patients with some active finger and wrist extension demonstrated positive, long-term effects in favor of ESS on functional capacity, but not on motor functions and the Stroke Impact Scale. Interestingly, the Stroke Impact Scale was positively influenced by the inactive placebo ESS, but the effect was temporary.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted as a retrospective subanalysis of an institutional review board–approved randomized controlled parallel group superiority trial (N=55). 14 The main trial had the following inclusion criteria: (1) sustained a single ischemic or hemorrhagic stroke during the 3- to 12-month period preceding enrollment; (2) inability at the time of screening to demonstrate active extension of the paretic metacarpophalangeal and interphalangeal joints at least 10° and the wrist, 20°; (3) baseline score of 47 or lower on the modified 30-item Fugl-Meyer Assessment (FMA) of UE motor function 17 ; and (4) 18 years of age or older. Exclusion criteria included (1) history of carpal tunnel syndrome and/or documented peripheral neuropathy; (2) addition or change in the dosage of drugs known to exert detrimental effects on motor recovery within 3 months of recruitment 18 ; and (3) aphasia or cognitive deficit severe enough to preclude informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study examining the effects of SS paired with intensive task-oriented motor training for participants with moderate to severely impaired UE motor function 3-12 months postictus found that SS paired with motor training led to greater motor improvement than sham SS paired with motor training. 14 The present study was a retrospective analysis of whether chronicity played a role in this outcome. In other words, the purpose of the present study was to evaluate if SS paired with task-oriented motor training had more benefit in early stages of recovery compared with later stages.…”
mentioning
confidence: 99%
See 1 more Smart Citation